PENGARUH VARIASI PRODUK, KUALITAS PELAYANAN, METODE PENGIRIMAN TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE APOTEK PT W DENGAN VARIABEL MODERASI PROMOSI: Pengaruh Variasi Produk, Kualitas Pelayanan, Metode Pengiriman terhadap Keputusan Pembelian di e-Commerce Apotek PT W dengan Variabel Moderasi Promosi - Kurniasih, Dian; Kosasih; Ahmar, Nurmala (UNIB Press, 2025)
The rapid growth of e-commerce in the pharmaceutical sector requires companies to understand key factors influencing consumer purchasing decisions. This study analyzes the effects of product variety, service quality, and delivery methods on purchasing decisions on PT W Pharmacy’s e-commerce platform, with promotion as a moderating variable. A quantitative approach using SEM-PLS was applied to data from 301 respondents. The results show that product variety has a positive and significant effect (coefficient = 0.207; t = 3.623; p = 0.000), as does service quality (coefficient = 0.157; t = 2.150; p = 0.032). Delivery methods show the strongest positive and significant effect (coefficient = 0.227; t = 4.223; p = 0.000). Promotion also directly has a positive and significant effect on purchasing decisions (coefficient = 0.362; t = 4.853; p = 0.000). As a moderating variable, promotion significantly strengthens the effect of service quality (coefficient = 0.196; t = 2.135; p = 0.033), does not significantly moderate product variety (coefficient = -0.090; t = 1.373; p = 0.170), and has a significant negative moderating effect on delivery methods (coefficient = -0.120; t = 2.019; p = 0.044). These findings emphasize the strategic role of delivery, service quality, and targeted promotion in enhancing online purchasing decisions